Forming Soy Malt Quality with Organic Growth Promoters - Yuliya Yu. Miller; Tatyana F. Kiseleva; Iulia V. Arysheva (Техника и технология пищевых производств)
Introduction. Soy is one of the most promising plant raw materials as it is rich in proteins and amino acids. However, its content of anti-nutritive compounds is too high to be used in food and beverage industry without precure. The research objective was to obtain soy-based malt with a high enzymatic activity, low content of anti-nutritional substances, and increased nutritional value. Study objects and methods. The study featured Far-Eastern soybean varieties and malt. It involved standard methods of quality control of raw materials, semi-finished products, and finished products of beer and alcohol industry, as well as the capillary electrophoresis, spectrophotometry, and potentiometry. Results and discussion. Germination of soybeans of all varieties contributed to the accumulation of hydrolytic enzymes and amino acids in the grain. The use of a complex of organic acids from the Krebs cycle at a concentration of 10–9 mol/dm3 at the soaking stage increased amylolytic, proteolytic, and lipoxygenase hydrolytic processes by 11, 22, and 12%, respectively. The level of urease, which correlates with the content of anti-nutritional substances, decreased by two times from the original level and was 0.4–0.5 units of pH. Germination stage fell down to 2.5–3 days, while the content of amino acids increased by 33–35% in comparison with unprocessed malt during soaking. Conclusion. The use of organic acids in soy malting improved the quality and technological indicators, increased the level of amino acids, and decreased the level of anti-nutritional substances, making soy malt suitable for beverage industry.